Replication competent viruses for cancer therapy: summarizes the molecular principles of modern viral therapy for cancer - Hernáiz Driever, Pablo (S. Karger, 2001)
Current cancer treatment approaches are characterized by very tight therapeutic indices and medical oncologists assign considerable care to treat adverse effects. A newly evolving concept in cancer therapy is the use of viruses. About 40 years ago initial trials based on the use of wild-type virus were not successful due to variable antitumoral effects and toxicity. The increase in our understanding of the molecular biology of malignant cells and viruses has now enabled researchers to design viruses that are capable of selectively destroying cancer cells and spare normal surrounding tissue. Oncolytic viruses either carry defined defects in their genomes which are specifically complemented by cancer cells, allowing their replication; or they are inherently selective for tumor cells. This book is the first to summarize the molecular principles of modern viral therapy for cancer. It reviews many of the replication-competent viruses currently being investigated for therapeutic use including herpes simplex virus, adenovirus, reovirus, parvovirus, vaccinia virus and Newcastle disease virus, and demonstrates how this approach is being translated to the clinic.Illustrating how virus-host interactions can be exploited for therapy, this book opens up new and promising perspectives for the treatment of cancer. It is therefore recommended reading for clinical investigators in the field of oncology, virologists, cancer immunologists and scientists working in regulatory agencies
Includes bibliographical references and index
Keywords: Replikation; Viren; Therapie; Krebs